Disaster Accountability Framework of Bangladesh: An Analysis of Strengths and Gaps (The Dhaka University Journal of Earth and Environmental Sciences, 2023)
This research aims to critically analyze the manifestation of accountability issues in disaster related major policies of Bangladesh as well as its field level implications. For that purpose, five major policies related to the Disaster Risk Reduction (DRR) of Bangladesh have been meticulously selected and analyzed. Critical analysis of the policy contents with regard to a model accountability framework has been principally adopted to derive the insights. Key Informant Interview (KII) with experts in the relevant fields has been considered for empirical data collection on accountability practices. The findings reveal existence of well-articulated accountability principles implanted into the policy dictates alongside weak institutional arrangements and governance mechanism to implement them at the empirical level. However, the remarkable progress of Bangladesh in disaster risk management against the partially dysfunctional accountability framework seemingly takes place by reaping benefits from indigenous knowledge and community based adaptive practices. The policy makers need to better understand the institutional mechanisms as well as the community level practices for DRR and finally mainstream them in the policy making process. The findings will potentially serve as a standard assessment of the current status of disaster risk governance in Bangladesh.The Dhaka University Journal of Earth and Environmental Sciences, Vol. 11(1), 2022: 69-80